HUBUNGAN ANTARA PENGETAHUAN DENGAN KESIAPSIAGAAN BENCANA COVID-19 PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA - Ardhya Wahyuningtyas Putri (2022)
The SARS-CoV-2 virus, which is easily transmitted and has been declared a pandemic, is the cause of COVID-19. Law Number 24 of 2007 concerning Disaster Management categorizes pandemics as non-natural disasters. Due to the high spread of COVID-19, the government has taken immediate steps to break the chain of spread of COVID-19 by making circulars and rules for implementing 5M (maintaining distance, washing hands, wearing masks, staying away from crowds, and reducing mobility). Good knowledge about COVID-19 is very necessary to support adequate preparedness. This research aims to determine the relationship between knowledge and COVID-19 disaster preparedness among UPN Veteran Jakarta medical faculty students. The research carried out was an observational analytical type using Cross Sectional as the research design, Simple Random Sampling as the sampling technique with a total of 278 respondents. The research instrument is a questionnaire. Data analysis uses univariate, bivariate analysis, and hypothesis verification uses the chi-square test. The test results showed that 258 respondents (92.8%) had good knowledge, 244 respondents (87.8%) were very ready to face COVID-19 with a bivariate analysis value of p = 0.000 (p < 0.05) which means there is a significant relationship between COVID-19 disaster knowledge and preparedness. Knowledge and preparedness are related, where when someone has good knowledge, that knowledge will support their preparedness or in other words, the more prepared the respondent will be in fighting COVID-19.